Meningkatkan Perkembangan Bahasa Indonesia Menggunakan Media Busy Book di TK Nurul Arafah - Annisa, Syafiqah; Karina Br Pa, Enda Rejekinta; Pinem, Rahel Jesiska; Hutagalung, Trisnawati (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Language is one of the most important aspects in early childhood development which must be stimulated optimally. Language is a tool for communicating, thinking and expressing oneself. Therefore, a teacher must stimulate the language development of his students through several learning methods and media. With learning media, namely busybooks, teachers can stimulate children's development with this media. Therefore, the researchers took the title of improving Indonesian language development in AUD by using busy book media in Nurul Arafah Kindergarten. From the research results, it was found that the use of busy books can help improve the language development of early childhood children in Nurul Arafah Kindergarten much better. This research also uses qualitative research methods where the research produces descriptive data in the form of written words and behavior observed during the research. Kata Kunci: Anak Usia Dini, Bahasa, Busy Book